Comparison between Gyko inertial sensor and Chronojump contact mat for the assessment of Squat Jump, Countermovement Jump and Abalakov Jump in amateur male volleyball players, amateur male rugby players and in high school students - Forza, J.; Edmundson, C. J. (Journal of Multidisciplinary Engineering Science and Technology, 2019)
The aim of this study is to compare vertical jump data obtained by two different measurement systems (Gyko accelerometer and Contact Mat) in order to assess the validity of the Gyko accelerometer as an alternative to the contact mat method. Ninety-six subjects (15.9 ± 1.4 years) performed a single Squat Jump (SJ), Countermovement Jump (CMJ) and Abalakov Jump (ABK). Jump height was simultaneously quantified with the Gyko system and the Chronojump Contact Mat (Criterion Device). Compared to the Contact Mat data, Gyko data determined no significant systematic bias for mean SJ (0.24 cm, p < 0.05, d = 0.04), CMJ (-0.01 cm, p < 0.05, d = 0.001) and ABK (0.001 cm, p < 0.05, d = 0.0002) height. Random bias was ± 5.69 cm for SJ, ± 4.59 cm for CMJ and ± 6.84 cm for ABK height. Pearson R-value demonstrated good to excellent correlation (SJ = 0.89; CMJ = 0.94; ABK = 0.92) between the two devices and Student`s T-test demonstrated no statistical difference between the data obtained (SJ = 0.42; CMJ = 0.97; ABK = 0.98) with the two different methods. Regression equations were provided to estimate the true jump height from Gyko derived data. Our findings indicate that Gyko system can be used interchangeably with Chronojump Contact Mat. It is suggested that practitioners apply the given correction equations for a more precise jump height estimation. The authors would suggest performing multiple set for assessing the endomorph subjects when assessing Squat Jump (SJ) because of increased errors due to soft-tissue movement artefact. Increasing the number of sets and then taking the mean value would decrease the random bias.